Cesarean Section Rates Differences among Hospitals in Jakarta - Basalamah A.; Suradi R.; Wiknyosastro G. H. (Indonesian Pediatric Society, 1995)
The incidence cesarean section (CS) has increased in the world as well as Indonesia. This fenomenon creates a concern among professionals. This study was undertaken to determine the incidence of CS and its indications among hospitals in Jakarta in 1992. Hospitals were divided into 3 groups according to the management and ownership: government (type A), semiprivate (type B) and private (type C) hospitals. Twelve hospitals belonged to type A, 17 to type B, and 34 to type C. Total deliveries in type A, B and C hospitals wereÂ respectively: 11 803; 19 130 and 17 665. The median number of deliveries was higher in type A than in type B or C. Most of type A hospitals (83.3%) and only 47.9% of type B and 11.8% of type C hospitals were open for referral cases. The mean CS rates were respectively 12.7%; 16,6% and 29.9% in type A, D. and C hospitals. Cephalopelvic disproportion was the most frequent indication in all 3 groups. In type A and B hospitals the second most frequent indication was antepartum hemorrhage while in type C hospitals it was previous CS. It is widely accepted that 80% of pregnancy with a CS scar can be delivered vaginally; so that the high incidenceof CS due to previous CS might be related to difference in interest or concept. In type C hospitals the 6th most frequent indication of CS was on mother's request, which was not found in type 8 or A hospitals. The length of stay was longer in type C than in type G or A hospitals.